Well Being Remaja Dalam Proses Pendidikan - Agustinus Riyanto (Universitas Katolik Musi Charitas, 2017)
Adolescence is transition state from childhood to adulthood. They strife to build their self identity. One of psychological aspects which influences the building self identity is self esteem. Adolescence maintains to strife for their psychological wellbeing in life and education. The aim of this quantitative study is to prove hypothetic question, is there any influence of self esteem and education system to the well being of senior high school adolescence? There were 299 participants (respondents) in this study. They consist of 163 male and 136 female students from Three Senior High Schools in Palembang. The instrument which is used to collect data is the questionnaire of Likert’s Scale. The reliability of the instruments is tested by using Alpha Cronbach formula. The result of the Cronbach Alpha for well being is 0.0876” and 0.942” for self esteem. Both of the collected data are analyzed with Analysis of Variances (Two way Anova ).The research found out self esteem have significance influence to well being with F = 53.946” and sig. value = 0.000” (< 0.05”). Education system also have significance influence to well being with F = 3.239” and sig. Value = 0.041” (< 0.05”). Meanwhile self esteem and education system all together have no significance influence to well being with F = 2.080” and sig. Value = 0.103” (> 0.05”).